2013
DOI: 10.1007/s00595-013-0768-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surgical extent and sex on the hepatic metastasis of colon cancer

Abstract: Purpose Extensive oncological surgeries were previously suggested to increase cancer recurrence rates. We herein studied the impact of different surgical procedures and sex on colorectal cancer liver metastasis, employing several tumor-inoculation approaches in BALB/c mice. Methods Experimental hepatic metastases of the syngeneic CT26 colorectal cancer line were induced either by intra-portal inoculation or intrasplenic inoculation, employing different tumor loads. Following intrasplenic inoculation, the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…No significant differences in metastatic development were evident between mild and extensive procedures, and the drug treatment was similarly efficacious in both conditions. In previous studies we also found similar developmental courses of experimental liver metastases in this tumor model employing surgical procedures of different extent (Sorski et al, 2014). Clinical studies comparing laparotomy to laparoscopy in colorectal cancer patients also did not show significant differences in long-term cancer outcomes (Jayne et al, 2010), despite many short-term advantages to minimal invasive surgeries (Biondi et al, 2013), as was also evident herein by lower levels of corticosterone in animals subjected to small incision.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…No significant differences in metastatic development were evident between mild and extensive procedures, and the drug treatment was similarly efficacious in both conditions. In previous studies we also found similar developmental courses of experimental liver metastases in this tumor model employing surgical procedures of different extent (Sorski et al, 2014). Clinical studies comparing laparotomy to laparoscopy in colorectal cancer patients also did not show significant differences in long-term cancer outcomes (Jayne et al, 2010), despite many short-term advantages to minimal invasive surgeries (Biondi et al, 2013), as was also evident herein by lower levels of corticosterone in animals subjected to small incision.…”
Section: Discussionsupporting
confidence: 80%
“…We have already reported in a previous study that females exhibit markedly fewer CT26 metastases than males, irrespective of (i) different injection procedures used, (ii) the load of CT26 cells challenge, and (iii) the magnitude of the surgical procedure (Sorski et al, 2014). We speculated that, among other mechanisms, males may be more prone to the impact of surgery while being administered with tumor cells, thus exhibiting more metastases.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, studies in our animal models, showed that adding laparotomy to a minor surgical procedure, or performing a more-traumatic surgery to excise a primary tumour 36 or administer syngeneic malignant cells, 124 resulted in worse immune outcomes, but did not significantly worsen cancer outcomes. Furthermore, in these studies, the use of a nonselective β-adrenergic antagonist and a COX2 inhibitor to attenuate the responses to surgery resulted in a similar degree of improvement in cancer outcomes (including overall survival rates) in minor and major surgical procedures.…”
Section: Surgical Aspects Affecting Recurrencementioning
confidence: 52%
“…Metastatic diseases occur in ~30-50% of CRC patients, either at the time of initial diagnosis or during follow-up (3,4). CRC metastasizes predominantly to the liver, and liver metastases account for at least two thirds of CRC deaths (3,5,6). Despite advances in research on primary CRC development, the mechanism for the progression from local disease to metastasis is not fully understood.…”
Section: Introductionmentioning
confidence: 99%